The effect of modified atmospheres on the mitochondrial respiratory function and cytochrome c oxidase activity from Rhyzopertha dominica (F.). (December 2022) - Levy-De la Torre, Víctor A.; Méndez-Romero, Ofelia A.; Muhlia-Almazán, Adriana T.; Cinco-Moroyoqui, Francisco J.; López-Zavala, Alonso A.; Ezquerra-Brauer, Josafat M.; Del Toro-Sánchez, Carmen L.; Martínez-Cruz, Oliviert
Abstract: The mitochondrial respiratory function and cytochrome c oxidase activity in the isolated mitochondria from Rhyzopertha dominica in hypoxia and hypercapnia was evaluated. Insects were exposed to three modified atmospheres treatments: hypoxia, hypercapnia, hypoxia-hypercapnia, and were compared to a control group (normoxia). Lactate concentration increased in insects under all conditions compared to the control group, which confirms that R. dominica switched its metabolism to anaerobic, supporting the effect of the modified atmospheres. Moreover, the respiratory function decreased in all modified atmospheres treatments up to 50% versus normoxia. Furthermore, all modified atmospheres treatments caused mitochondria uncoupling and a decrease up to three-fold in the cytochrome c oxidase activity compared to normoxia. Besides the lesser O2 availability, this response was possible due to low activity in the electron transport chain, low concentrations of metabolites that participate in the energy-gaining process (glycolysis and the Krebs cycle), or a decrease in ATP production. This information can contribute to the development of new environmental alternatives in order to exterminate or diminish pests in grain warehouses. Highlights: Lactate increased in Rhyzopertha dominica exposed to hypoxia and hypercapnia. Insects decreased mitochondria oxygen consumption in hypoxia and hypercapnia. Insects' mitochondria were uncoupled by hypoxia and hypercapnia. Cytochrome c oxidase activity decreased due to hypoxia and hypercapnia.